Does compulsive behavior in Anorexia Nervosa resemble an addiction? A qualitative investigation - Godier, Lauren R.; Park, Rebecca J. (Frontiers in Psychology, 2015)
The characteristic relentless self-starvation behaviour seen in Anorexia Nervosa (AN) has been described as evidence of compulsivity, with increasing suggestion of parallels with addictive behaviour. This study used a thematic qualitative analysis to investigate the parallels between compulsive behaviour in AN and Substance Use Disorders (SUD). Forty individuals currently suffering from AN completed an online questionnaire reflecting on their experience of compulsive behaviour in AN. Eight main themes emerged from thematic qualitative analysis; compulsivity as central to AN, impaired control, escalating compulsions, emotional triggers, negative reactions, detrimental continuation of behaviour, functional impairment, and role in recovery. These results suggested that individuals with AN view the compulsive nature of their behaviour as central to the maintenance of their disorder, and as a significant barrier to recovery. The themes that emerged also showed parallels with the DSM-V criteria for Substance Use Disorders (SUDs), mapping onto the four groups of criteria (impaired control, social impairment, risky use of substance, pharmacological criteria). These results emphasise the need for further research to explore the possible parallels in behavioural and neural underpinnings of compulsivity in AN and SUDs, which may inform novel treatment avenues for AN.